Association Between Diverticular Disease and Abdominal Aortic Aneurysms: Pooled Analysis of Two Population Based Screening Cohorts. (December 2017) - Mark-Christensen, Anders; Lindholt, Jes Sanddal; Diederichsen, Axel; Steffensen, Flemming Hald; Busk, Martin; Frost, Lars; Urbonaviciene, Grazina; Lambrechtsen, Jess; Egstrup, Kenneth; Laurberg, Søren
Abstract : Background: The aetiology of abdominal aortic aneurysms (AAA) is multifactorial, and many risk factors are shared with diverticular disease. It is unknown whether an independent association exists between these conditions. Methods: Individuals enrolled in two Danish population based randomised AAA screening trials and assigned to cross sectional screening and evaluation of cardiovascular risk factors were identified. Diagnoses of diverticular disease were interrogated from a national patient registry covering the period from 1977 to the screening date. Adjusted odds ratios (aOR) and hazard ratios (aHR) with 95% CI were calculated as risk measures. Results: 24, 632 individuals (median age, 69 years) were included. At screening, 687 patients had pre-existing diverticular disease. Patients with diverticular disease were more likely to have AAA at screening compared with those without diverticular disease (5.2% vs. 3.3%) (OR 1.61, 95% CI 1.14–2.27). This association persisted after adjusting for potential confounders (aOR 1.49, 95% CI 1.04–2.12) and on sensitivity analyses. The association was most pronounced for those with a diagnosis of diverticular disease for at least 10 years (aOR 2.56, 95% CI 1.49–4.38). Following screening, 6.2% of patients with diverticular disease and AAA experienced aneurysm rupture, compared with 2.2% of patients with AAA without diverticular disease (aHR 4.1, 95% CI 1.6–10.8). Conclusion: An association was found between diverticular disease and AAA in a large population based cohort. Biological causality remains to be established, and a potential impact of diverticular disease on the natural history of AAA needs to be explored further.